Vulneración a la normativa constitucional del debido proceso con el numeral 2 art. 599 del código orgánico integral penal - León Macas, Ángel Stalin (2016)
In recent years in Ecuador they have been several legal changes so that the adoption of the Constitution of the Republic of Ecuador in 2008, an emphasis was given never before seen in our cuo status, so entrenched for a long time; but nevertheless, these new rules that come with strength, power, have managed to banish an existing model, to replace it by this new legal culture in a guarantor State Constitutional rights. In the constitutional state must exist a set of principles and guarantees, which in practice make rights have their recognition with the special force, which when violated these are claimed even coercively, now we can say that there is a contemporaneity of law in Ecuador. the direct application of the constitutional norm is established, the other below the highest standard rules should be subject to it, hence the importance of the work possessed by members of the National Assembly in approving the laws or regulations of general interest because among other things regulates the exercise of fundamental rights, we must also consider that the Constitution guarantees without discrimination the effective enjoyment of the rights established in it and in international instruments. Among the rights enshrined in the Constitution is the right to due process, constitutionally recognized explicitly, the same as is violated in the new Code of Criminal Integral. The work contains aspects that allow review why the problem, its causes and consequences. The methods provided obtaining valid data, and verifiable, achieving subjectivity away and get real results through orderly procedures designed to produce interesting results